Implementation of Waqf Management in The Development of Islamic Education - Larasati Nur Kharomah; Achyar Zein; Syafruddin Syam (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2022)
This article aims to determine the waqf management at the Al-Kaffah Binjai City Waqf Foundation and the development of Islamic education at the Al-Kaffah Binjai City Waqf Foundation. This study uses qualitative methods with the type of field research. Researchers perform data collection techniques through interviews, observation, and documentation. Data analysis techniques are carried out by reducing data and presenting data and conclusions. There are two specific findings in this study, namely: 1) Waqf management conducted by Al-Kaffah Binjai City Waqf Foundation using the PIE model (planning, implementation, and evaluation). 2) development of Islamic education through waqf in Al-Kaffah Binjai City Waqf Foundation consists of a curriculum and Human Resource Development.